Online learning - Global Challenges and Opportunities for Students in Higher Education amid the COVID-19 Pandemic: The Libyan Context - Abdelbasit Gadour (Britain International for Academic Research (BIAR) Publisher, 2021)
The spread of COVID-19 has had psychological effects on higher education students globally reflected in high level of anxiety associated with worries of failing to complete their studies (Holmes et al., 2020; Sawahhel, 2020). Due to COVID-19 all universities in Libya were closed for ten months causing a massive impact and leaving about quarter a million students without education. However, during this period some universities took preventive measures and maintained functioning from a distance. An attempt was made in this study to explore higher education students’ attitudes toward online learning and appreciate more the advantages and challenges associated with online learning. Of the 100 questionnaires sent out to university students, 58 responded back of whom 40 undergraduate and the remaining postgraduate students. The results of this study suggested that students are more interested in conventional way of learning in favour of face-to-face communication with tutors and peers as opposed to remote learning. For online learning to be successful in Libya, universities ought to upgrade their educational mode of delivery making the learning contents and assessment more desirable and responsive to the needs of the changing times. Furthermore, students must be technically and financially supported with unlimited access to internet.